Effect Of Reward And Punishment On Employee Performance Of PT. Revelation Of Septyan Bengkulu - Rudi Afriansa; Neri Susanti; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2023)
Performance is a benchmark for employees in carrying out targeted tasks to be completed. Efforts to conduct performance appraisals are important by knowing the right performance measurements. The purpose of this study was to determine the effect of reward and punishment on the performance of employees of PT. Wahyu Septyan Bengkulu.The sample in this study was 60 employees of PT. Wahyu Septyan Bengkulu. The data was collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results showed that the regression value showed a positive influence between Reward and Punishment on employee performance at PT. Wahyu Septyan Bengkulu because the direction of the regression has a positive direction, namely Y = 9.920 + 0.316X1 + 0.455X2 + e. Reward has a significant effect on employee performance at PT. Wahyu Septyan Bengkulu, because the significant value of 0.007 is smaller than 0.05. This means that the increasing attention to employee rewards will increase the performance of employees of PT. Wahyu Septyan Bengkulu. Punishment has a significant effect on employee performance at PT. Wahyu Septyan Bengkulu because the significant value of 0.000 is smaller than 0.05. This illustrates that the more the employee's Punishment is improved, the performance will also increase. Reward and Punishment have a significant effect together on employee performance at PT. Wahyu Septyan Bengkulu, thus the initial hypothesis proposed is proven (Ha is accepted). That is, there is a significant influence between Reward and Punishment on performance together. The coefficient of determination of R square is 49.8% while the rest (100-49.8% = 50.2%) is influenced by other causal factors not examined in this study.